After the June War: Peace or Justice, Conflict Management or Democracy in Palestine-Israel?. Issue 2 (November 2017) - Beitzel, Terry
Abstract : The post-June War period becomes predominantly, though not exclusively, an 'Israeli-Palestinian' conflict rather than an 'Arab-Israeli' conflict. What sort of state is the Palestine Liberation Organisation (PLO) wishing to establish? Since at least 1968, The Palestinian leadership has made explicit statements concerning governance, especially in favour of democracy and justice. Why was this ignored? The first aim of this study is not to draw out the situated nuances and contours for a complete description of the Palestinian perception of governance and international law, rather the aim is thematically to examine the Palestinian support for a more democratic form of governance. Secondly, this study attempts to examine the official Israeli record and reaction (or lack thereof) to these statements made by the Palestinians. Finally, these findings will be compared to conflict management and democratisation. The study ends with a question to the reader: what if more energy were placed into supporting democracy rather than managing conflict? Or, said another way, justice rather than peace?